2010
DOI: 10.1108/17590831011055860
|View full text |Cite
|
Sign up to set email alerts
|

The constructs mediating religions' influence on buyers and consumers

Abstract: Purpose -There is limited conceptual and theoretical knowledge among marketers and practitioners regarding the measurement of religious influences in consumer market-place behaviours. The purpose of this paper is to review religious factors that appear to influence buyer and consumer behaviour in the light of findings from marketing and religious psychology. Design/methodology/approach -The paper utilises academic databases to search for marketing and religious psychology papers that deal with influences of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(123 citation statements)
references
References 24 publications
9
104
1
9
Order By: Relevance
“…The ethical elements have become the prominent element in marketing approach where it may affect the sales performance of the marketers (Wotruba, 1990;Piercy & Lane, 2007;Nazlida & Mizerski, 2010;Arham, 2010;Fu et al, 2010). In addition, the marketers (Takaful agents in the context of this research) must sincere in addressing their customers' needs and prepare themselves with enough knowledge on Takaful and the financial sector besides enhancing their marketing skills (Nafik et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The ethical elements have become the prominent element in marketing approach where it may affect the sales performance of the marketers (Wotruba, 1990;Piercy & Lane, 2007;Nazlida & Mizerski, 2010;Arham, 2010;Fu et al, 2010). In addition, the marketers (Takaful agents in the context of this research) must sincere in addressing their customers' needs and prepare themselves with enough knowledge on Takaful and the financial sector besides enhancing their marketing skills (Nafik et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…A review of past literature has revealed a large volume of research in marketing that indicate ethics as among the main issues in marketing and sales (Wotruba, 1990;Piercy & Lane, 2007). However, only a few of these researches have included religious elements in their domain (Nazlida & Mizerski, 2010). On that note, Arham (2010) suggests that Islamic teachings could be implemented in the current marketing conjecture.…”
Section: Measure Of Islamic Relationship Marketingmentioning
confidence: 99%
See 2 more Smart Citations
“…Petrovici and Marinov (2007) reported that beliefs about advertising were significantly shaping global or GARA. Pollay and Mittal (1993) considered three kinds of advertising beliefs i.e., product information, image or social role and hedonic or sensory pleasure as strong predictor of attitude towards general advertising. Advertising has an entertainment value which makes a positive effect on the GARA.…”
Section: Hypotheses and Conceptual Modelmentioning
confidence: 99%